LYSINE REQUIREMENT IN THE DIET OF GLASS EELS, ANGUILLA BICOLOR, AGAINST GENE EXPRESSION ASSOCIATED WITH GROWTH HORMONE - Norman Arie Prayogo; Slamet Budi Prayitno; Tjahyo Winanto; Taufan Harisam; Ren Fitriadi; Baruna Kusuma; Purnama Sukardi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Traditional eel farmers face the problem of poor quality and high price of commercial glass eel diet, this feed has produced poor fish performance, as well. The lack of essential amino acids may be the cause. Molecular methods are used to determine the rapid response of glass eels to a formulated diet. The purpose of this study was to determine how the effect of adding lysine to commercial feed affects the expression of genes related to growth hormone GH. Pasta feed was given to glass eels (1600 heads) which were cultured for 60 days. The cylindrical plastic ponds were framed with steel and covered with HDPE plastic (300μm) in size {(3.14cm) x (85cmx85cm) x (60cm)} filled with water 907,460 L ≈ 0.91 m3. Real time RT-PCR results in GH suggest that the level of lysine (2%) added to the diet has strong effect on GH gene expression during eight weeks cultivation.